On the Resistance-Harary Index of Graphs Given Cut Edges. (21st December 2017) - Wang, Hongzhuan; Hua, Hongbo; Zhang, Libing; Wen, Shu
Abstract : Graphs are often used to describe the structure of compounds and drugs. Each vertex in the graph represents the molecule and each edge represents the bond between the atoms. The resistance distance between any two vertices is equal to the resistance between the two points of an electrical network. The Resistance-Harary index is defined as the sum of reciprocals of resistance distances between all pairs of vertices. In this paper, the extremal graphs with maximum Resistance-Harary index are determined in connected graphs with given vertices and cut edges.